The Influence of On-Time Performance, Flight Routes, and Competitive Prices on Load Factor on Citilink Airlines - R.Iskandar Ali; Taufik Taufik; Juliater Simarmata (Dinasti Publisher, 2024)
The article on the influence of on-time performance, flight routes and competitive prices on load factors on Citilink airlines is a scientific literature review article within the scope of marketing management science. This article aims to create a hypothesis regarding the relationship between factors, which can then be used for further research in the field of marketing management. Descriptive qualitative research methodology was used in this research. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The findings of this research are as follows: 1) On time performance influences the load factor of Citilink airline; 2) Flight routes influence the load factor of Citilink airlines; and 3) Competitive prices influence the load factor of Citilink airlines.